3D Graphene Composites for Efficient Electrochemical Energy Storage. Issue 15 (6th June 2018) - Bu, Fanxing; Shakir, Imran; Xu, Yuxi
Abstract: 3D graphene (3DG) composites have attracted significant interest for electrochemical energy storage applications, including supercapacitor, lithium‐/sodium‐ion battery, lithium–sulfur battery, and lithium–oxygen battery. With an interpenetrating network structure of conductive skeleton of graphene and highly continuous porous channels, the 3DG composites can not only ensure efficient electron and ion transport, but also retain structural stability of electrode materials during the electrochemical reactions. Rapidly growing efforts are seen in the design and synthesis of various 3DG composites with novel structures for diverse electrochemical energy storage devices in recent years. To promote deeper understanding and inspire further development of this exciting class of materials, the recent progress on preparation strategies of 3DG composites with applications in electrochemical energy storage is reviewed. A particular emphasis is placed on the detailed physicochemical mechanisms about the synthesis and structural evolution of 3DG composites and their impact on the electrochemical performance. As a conclusion, a brief perspective on future opportunities and challenges is given. Abstract : With highly continuous graphene network, hierarchically interconnected porous channels, and robust mechanical strength, 3D graphene (3DG) composites hold great potential for high‐performance electrochemical energy storage devices. In this review, recent progress on preparation strategies of 3DG composites and their applications in electrochemical energy storage are discussed, followed by a brief perspective on future opportunities and challenges.